2013
DOI: 10.1371/journal.pmed.1001403
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Atypical Antipsychotic Treatment for Major Depressive Disorder: A Meta-Analysis of Depression, Quality of Life, and Safety Outcomes

Abstract: In a systematic review and meta-analysis, Glen Spielmans and colleagues find that adjunctive atypical antipsychotic medications are associated with small-to-moderate improvements in depressive symptoms in patients with depression, but there is little evidence for improvement on measures of quality of life, and these medications are linked to adverse events such as weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(142 citation statements)
references
References 78 publications
4
131
0
1
Order By: Relevance
“…Three meta-analyses of the use of atypical antipsychotics for augmentation in TRD have been published [19,93,94]. The first meta-analysis by Papakostas et al [93] showed a pooled response rate of 57% for patients given atypical antipsychotics, compared with 35% for placebo.…”
Section: Resultsmentioning
confidence: 99%
“…Three meta-analyses of the use of atypical antipsychotics for augmentation in TRD have been published [19,93,94]. The first meta-analysis by Papakostas et al [93] showed a pooled response rate of 57% for patients given atypical antipsychotics, compared with 35% for placebo.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is no firm empirical basis for placing undue value on this measure as opposed to other outcomes examined in our analysis. Indeed, in adult depression research, it has been argued that measures outside of clinician-rated depression scales add important information in understanding overall well-being [7,9,10,11]. …”
Section: Discussionmentioning
confidence: 99%
“…Because we found very few measures within each aforementioned category (including no positive affect measures), we opted to pool these measures as a proxy for overall well-being. In a recent meta-analysis of atypical antipsychotic augmentation treatment for adult depression, measures of quality of life and functioning were similarly pooled to create a composite for well-being [9]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analyses have demonstrated greater efficacy of these medications versus placebo as augmentation in patients with treatment-resistant MDD. Nelson and Papakostas 50 found ORs of 1.69 and 2.00 for response and remission, respectively; Spielmans et al 51 also showed statistically significant effects on response and remission rates as well as clinician-rated depression severity measures.…”
Section: Augmentation Strategiesmentioning
confidence: 95%